2022
DOI: 10.3390/cells11091409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traumatic Brain Injury on the Gut Microbiota Composition and Serum Amino Acid Profile in Rats

Abstract: Traumatic brain injury (TBI) heavily impacts the body: it damages the brain tissue and the peripheral nervous system and shifts homeostasis in many types of tissue. An acute brain injury compromises the “brain–gut-microbiome axis”, a well-balanced network formed by the brain, gastrointestinal tract, and gut microbiome, which has a complex effect: damage to the brain alters the composition of the microbiome; the altered microbiome affects TBI severity, neuroplasticity, and metabolic pathways through various bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Increases in bacteria belonging to the Erysipelotrichaceae family such as Faecalibaculum , as well as increases in Lachnospiraceae , both of which are considered ‘beneficial butyrate producers’ have been shown to be increased following mTBI in rodents [ 40 ] as seen in the present study. Conversely, it is commonly reported that following severe TBI there is a reduction in these ‘beneficial’ bacteria, up to 30 days following injury [ 18 , 81 ]. The exact mechanisms driving this increase in beneficial butyrate producing bacteria after injury is unknown, however, it may be a protective response to compensate for the secondary injury cascade that follows mTBI [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in bacteria belonging to the Erysipelotrichaceae family such as Faecalibaculum , as well as increases in Lachnospiraceae , both of which are considered ‘beneficial butyrate producers’ have been shown to be increased following mTBI in rodents [ 40 ] as seen in the present study. Conversely, it is commonly reported that following severe TBI there is a reduction in these ‘beneficial’ bacteria, up to 30 days following injury [ 18 , 81 ]. The exact mechanisms driving this increase in beneficial butyrate producing bacteria after injury is unknown, however, it may be a protective response to compensate for the secondary injury cascade that follows mTBI [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Peptococcaceae and Eubacterium genera of the Firmicutes phylum were also increased; however, their roles in determining TBI outcome were unclear (Houlden et al, 2016;Treangen et al, 2018). Interestingly, a clinical study in NCAA Football players with found a similar pattern of change in Lachnospiraceae bacterium A2 and Lactobacillus johnsonii after concussion (Soriano et al, 2022) as the preclinical study from Yanckello et al (2022) severe TBI animal models (Frankot et al, 2022;Treangen et al, 2018) except for the Prevotellaceae family (Taraskina et al, 2022).…”
Section: Tbi Induces Gut Dysbiosismentioning
confidence: 95%
“…Interestingly, a clinical study in NCAA Football players with found a similar pattern of change in Lachnospiraceae bacterium A2 and Lactobacillus johnsonii after concussion (Soriano et al, 2022) as the pre‐clinical study from Yanckello et al (2022) modelling a milder injury. Conversely, a clinical study in patients with chronic moderate–severe TBI did not find similar microbiota changes (Urban et al, 2020) to those in more severe TBI animal models (Frankot et al, 2022; Treangen et al, 2018) except for the Prevotellaceae family (Taraskina et al, 2022).…”
Section: Tbi Disrupts Microbiota–gut–brain Homeostasismentioning
confidence: 97%
“…We therefore supposed that blood concentrations of amino acids might bear some relation to the progression of TBI, thus presenting a potential diagnostic or prognostic tool. Indeed, several prior studies have examined changes in plasma or serum amino acid levels after TBI in humans (Deutschman, 1987;Flakoll et al, 1995;Petersen et al, 1996;Vuille-Dit-Bille et al, 2012;Jeter et al, 2013) and in animal models (Louin et al, 2007;Zheng et al, 2017;Taraskina et al, 2022). In a piglet TBI model, plasma levels of glycine, ornithine, and the nonproteinogenic amino acid taurine at 24 h post-injury correlated with central injury in a regression model (Hajiaghamemar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%